2022
DOI: 10.1113/ep090580
|View full text |Cite
|
Sign up to set email alerts
|

The influence of alcohol on genioglossus single motor units in men and women during wakefulness

Abstract: Alcohol worsens obstructive sleep apnoea (OSA). This effect is thought to be due to alcohol's depressant effect on upper airway dilator muscles such as the genioglossus, but how alcohol reduces genioglossal activity is unknown. The aim of this study was to investigate the effect of alcohol consumption on genioglossus muscle single motor units (MUs). Sixteen healthy individuals were studied on two occasions (alcohol: breath alcohol concentration ∼0.07% and placebo). They were instrumented with a nasal mask, fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…A composite of the four recordings allowed for the estimation of global genioglossal activity, whereas spike sorting was used to discriminate motor units from different tongue regions, with motor units classified into standard predetermined categories related to the respiratory cycle. Surprisingly, Avraam et al (2023) found only modest, non-significant effects of alcohol consumption on global genioglossal EMG activity.…”
Section: Multiple Factors Contribute To Airway Vulnerability and Prop...mentioning
confidence: 72%
See 4 more Smart Citations
“…A composite of the four recordings allowed for the estimation of global genioglossal activity, whereas spike sorting was used to discriminate motor units from different tongue regions, with motor units classified into standard predetermined categories related to the respiratory cycle. Surprisingly, Avraam et al (2023) found only modest, non-significant effects of alcohol consumption on global genioglossal EMG activity.…”
Section: Multiple Factors Contribute To Airway Vulnerability and Prop...mentioning
confidence: 72%
“…Therefore, studies of the effects of alcohol on genioglossus EMG and motor unit activity throughout the sleep-wake cycle in healthy participants and people with OSAS are warranted. Notwithstanding the findings of Avraam et al (2023), evidence that alcohol consumption worsens the severity of OSAS counsels that a 'nightcap' is contraindicated in people at risk of obstructive airway events and is probably best avoided even by others!…”
Section: Multiple Factors Contribute To Airway Vulnerability and Prop...mentioning
confidence: 99%
See 3 more Smart Citations